Excessive Use of WeChat at Work Promotes Creativity: The Role of Knowledge Sharing, Psychological Strain - Zhang, Huiqin; Wang, Meng; Li, Meng; Chen, Xudong (Frontiers in Psychology, 2021)
The pervasive nature of social media can result in excessive use and addiction, but whether excessive use of social media is good or bad for individuals’ creativity is unclear. This study explored the direct and indirect impact of excessive use of WeChat on individuals’ creativity in workplace, focusing on how excessive use of WeChat promotes or restrains creativity through knowledge sharing and psychological strain. Based on the person-environment fit model and motivation theory, this study examined the three paths of excessive WeChat use affecting individuals’ creativity in workplace. We used the structural equation model to test our research model. A survey of 218 employees revealed that excessive WeChat use directly promotes creativity and indirectly improves creativity via knowledge sharing, but excessive WeChat use does not lead to psychological strain. These findings, obtained by theoretically and empirically investigating the positive outcomes of excessive WeChat use, suggest an upside to excessive WeChat use. The implications and limitations of this study and future research on excessive use behavior are also discussed.